Managing complexity in organizations : text and cases - 523466 Nedopil, Christoph; Steger, Ulrich; Amann, Wolfgang (Houndmills, Basingstoke, Hampshire [England] ; New York : Palgrave Macmillan, 2011)
Includes bibliographical references (p. 369-381) and index